2022
DOI: 10.1515/cclm-2021-1226
|View full text |Cite
|
Sign up to set email alerts
|

The flagging features of the Sysmex XN-10 analyser for detecting platelet clumps and the impacts of platelet clumps on complete blood count parameters

Abstract: Objectives Platelet clumps present in anticoagulant specimens may generate a falsely decreased platelet count and lead to an incorrect diagnosis. A clear understanding of the ability of a haematology analyser (HA) to detect platelet clumps is important for routine work in the clinical laboratory. Methods Citrate-anticoagulated whole-blood samples were collected from various patients as a negative group. Adenosine diphosphate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Figure 4 shows that the CNN algorithm has no positive threshold determined by the platelet count, which is an algorithmic limitation of the XN-10 that was discussed in our previous study. 11 The above results indicate that the CNN can accurately detect platelet clumps using the optical information from the dedicated leukocyte channels and that the SSC and FSC of the WNR channel are the most suitable data for CNN training.
Figure 2.The average ROC curves of the training groups. The average ROC curves of the CNNs trained by scattergrams from the WNR and WDF channels are plotted as solid and dashed lines, respectively.
…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Figure 4 shows that the CNN algorithm has no positive threshold determined by the platelet count, which is an algorithmic limitation of the XN-10 that was discussed in our previous study. 11 The above results indicate that the CNN can accurately detect platelet clumps using the optical information from the dedicated leukocyte channels and that the SSC and FSC of the WNR channel are the most suitable data for CNN training.
Figure 2.The average ROC curves of the training groups. The average ROC curves of the CNNs trained by scattergrams from the WNR and WDF channels are plotted as solid and dashed lines, respectively.
…”
Section: Resultsmentioning
confidence: 80%
“…The platelet aggregation rate (PAR) of each imitated PCD sample was calculated using the formula PAR = (Pb – Pa)/Pb, in which Pb represents the platelet count before ADP induction and Pa represents the platelet count after ADP induction. 11 The criteria for a PCD sample to be used for training were as follows: (a) The PAR was higher than 10%. (b) At least 1 platelet clump (containing a minimum of 3 platelets) was observed in the blood smear within 50 high magnification fields.…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Xu et al, 12 on the samples with low platelet counts showed that the total sensitivities of the platelet, CLP and platelet abnormal flags on platelet histogram/platelet distribution curve were 80.01% and 100%, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Various studies have been conducted to explore PTCP detection, with varying sensitivity and specificity found with different devices. The sensitivity and specificity of the Sysmex instrument (Sysmex, Kobe, Japan) were 0.626 and 0.947, respectively, when platelet aggregation was induced using adenosine diphosphate in citrate-anticoagulated whole blood samples [17]. In a comparative analysis of the usefulness of platelet-clump flagging among the Sysmex, Beckman Coulter, and ADVIA (Siemens Healthcare Diagnostics, Eschborn, Germany) CBC analyzers, the Sysmex analyzer demonstrated the highest sensitivity of 67% [18].…”
Section: Discussionmentioning
confidence: 99%